Studies Towards Sulfate Sensing by Voltammetry at Liquid-liquid Interfaces - Kalaei, Nasib (Curtin University, 2023)
Detection of anions is of considerable importance for their clinical and environmental applications. The focus of this thesis is investigation of electrochemical methods for sensing of sulfate ions. One of the main applications of sulfate sensing is in water recycling plants and using of sulfate as an indicator to assess the performance of reverse osmosis membranes which are used as a powerful barrier to remove contamination from wastewater. The basis of electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) is the occurrence of ion transfer at the polarizable interface, which is formed between two solutions, one aqueous and the other organic, when they are brought into contact. This provides the possibility of anion detection. Amongst various anions, the anions with low hydration energy can be detected more easily because of their low hydrophilicity. However, detection of hydrophilic anions, which have greater hydration energy, is more challenging than for other anions. Among different inorganic anions, sulfate has the highest hydration energy and consequently is one of most challenging anions for detection. The results presented within this thesis provide a basis for anion sensing by simple, portable, and rapid electrochemical methods based on voltammetry. Sulfate sensing was achieved by ion transfer at thin films on electrodes containing new Ru complexes as ion to electron transducers.